An investigation into linguistic features in advertising slogans of cosmetic products in English and Vietnamese - Lê, Lê Lộc Uyển. (2014)
This thesis was to study the lexical, syntactic and stylistic features of cosmetic advertising slogans in English and Vietnamese. The descriptive and contrastive methods were used in combinations with the qualitative and quantitative approach. The findings of this study were presented based on a collection of 200 samples in English and Vietnamese (100 in English and 100 in Vietnamese) taken from the Internet, magazines and newspapers. The thesis aimed at withdrawing the similarities and differences in lexical, syntactic and stylistic features of cosmetic advertising slogans in English and Vietnamese. Lexically, the advertising slogans were divided into monosyllabic verbs, weasel words, favorable words (including adjectives and comparative and superlative degrees) and personal pronouns. Syntactically, the analyzed advertising slogans were presented in forms of verb phrase, noun phrases, imperative and declarative mood, short sentences, simple sentences and elliptical sentences. Stylistically, the advertising slogans were categorized into five stylistic fields including repetition, hyperbole, rhetorical questions, rhyme and parallelism. The thesis also discovered the underlying cultural features to explain the similarities and differences in lexical, syntactic and stylistic features of cosmetic advertising slogans in English and Vietnamese. Besides, the study put forward some implications to help advertisement composers in writing efficient cosmetic advertising slogans in English and Vietnamese. Moreover, the thesis offered some pedagogical implications from the English and Vietnamese cosmetic advertising slogans for English and Vietnamese teaching and learning.